Paranasal sinuses in patients with chronic rhinosinusitis, Tanzania - Enica R.Massawe; Happy E Somboi; Asterius Muganyizi; Petra Joseph (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2024)
Introduction: Chronic rhinosinusitis is inflammation of the nasal cavity and paranasal sinuses that lasts for at least twelve weeks. Paranasal sinus variations account for various pathologies, including chronic rhinosinusitis. This study assessed the anatomical variations of paranasal sinuses among patients with chronic rhinosinusitis attending otorhinolaryngology services in a tertiary hospital in Tanzania. Method: This was a descriptive prospective cross-sectional study of 120 patients aged 15 years and above who fulfilled the Rhinosinusitis Task Force criteria. A structured checklist was used to collect socio-demographic characteristics and clinical presentations. Cone-beam computed tomography scan and the Lund-Mackay scoring system were used. Data analysis was done using SPSS version 26, and p-values <0.05 were considered statistically significant. Results: A total of 120 patients were enrolled with a median age of 37 (IQR 27-52) years, with 40% aged 30-49 years. There were 65 (54.2%) males, and 55 (45.8%) females. Maxillary sinuses were affected in 85.8% of all patients with chronic rhinosinusitis. The overall proportion of anatomical variation was 53.3%, with concha bullosa, deviated nasal septum, Onodi cells, and septal spur being the most common, accounting for 40.6%, 25.0%, 23.4%, and 20.3%, respectively. Twenty-four patients with concha bullosa had chronic maxillary rhinosinusitis, with 14 (58.3%) having ipsilateral rhinosinusitis. Conclusion: Half of the patients had one or more paranasal sinus anatomical variations. The most common variants were concha bullosa followed by deviated nasal septum. Onodi cells and septal spurs were rarely identified. Most patients with concha bullosa had ipsilateral maxillary sinusitis.